Geomorfologia e tectônica da Folha Jacumã 1: 25.000 - Barbosa, Maria Emanuella Firmino (2013)
The present study refers to the geomorphological and morphometric characterization of the region encompassed by the Jacumã Chart (SB-25-Y-C-III-3-NE), located in the state of Paraíba. The use of GIS techniques for morphotectonic evaluation, besides aiming to reinforce the hypothesis raised by previous studies, is considered relevant because the products generated are formidable to concisely highlight the morphology of the relief, where the influence of tectonics in its configuration and arrangement is conspicuous. The techniques used in this study consisted of the elaboration and analysis of the hypsometric, declivity, and slopes orientation charts; as well as the analysis of the roughness and disposition of the relief, and the analysis of topographic profiles and 3D models generated in this study. For producing the above products were utilized manual vectorization in screen of Jacumã topographic map with scale of 1:25,000 and equidistance between the level curves of 10m, and Spring 5.1.7 software. The results obtained from the analysis of the products showed that in the central portion of the area there is a strong structural control on the right bank tributaries of the Guruji river, where they have a marked altimetric unevenness, high steep slopes, and deep fluvial cuts and they are more numerous and enlarged than the left bank tributaries. At the end of the course of the Guruji river, there is a steep slant of approximately 90º, where its direction changes abruptly from W-E to S-N. Another anomalous point observed in the area was a large incision of the tributaries of the whatershed of Graú river, in the southern portion of the studied area, where the morphology of the relief changes abruptly from tabular to hilly and its flow is steeply slanted in its low course, changing its direction from W-E to NNWSSE.